Anthropomorphism brings us closer: The mediating role of psychological distance in User–AI assistant interactions. (May 2021) - Li, Xinge; Sung, Yongjun
Abstract: In the current era, interacting with Artificial Intelligence (AI) has become an everyday activity. Understanding the interaction between humans and AI is of potential value because, in future, such interactions are expected to become more pervasive. Two studies—one survey and one experiment—were conducted to demonstrate positive effects of anthropomorphism on interactions with smart-speaker-based AI assistants and to examine the mediating role of psychological distance in this relationship. The results of Study 1, an online survey, showed that participants with a higher tendency to anthropomorphize their AI assistant/s evaluated it/them more positively, and this effect was mediated by psychological distance. In Study 2, the hypotheses were tested in a more sophisticated experiment. Again, the results indicated that, in the high-anthropomorphism (vs. low-anthropomorphism) condition, participants had more positive attitudes toward the AI assistant, and the effect was mediated by psychological distance. Though several studies have demonstrated the effect of anthropomorphism, few have probed the underlying mechanism of anthropomorphism thoroughly. The current research not only contributes to the anthropomorphism literature, but also provides direction to research on facilitating human–AI interaction. Highlights: Anthropomorphism has a positive effect on the evaluation of AI assistants. Psychological distance plays a mediating role in this relationship. Uncanny response does not correlate with anthropomorphism.